2003
DOI: 10.4049/jimmunol.171.8.4352
|View full text |Cite
|
Sign up to set email alerts
|

Selective Depletion of Nonspecific T Cells During the Early Stage of Immune Responses to Infection

Abstract: Transient T cell depletion occurs before the development of an effective immune response to infection. In this study we show that most T cells, regardless of specificity, are induced to express early activation markers soon after infection with Listeria monocytogenes or lymphocytic choriomeningitis virus. Ag-specific T cells are further activated to display late activation markers and undergo extensive proliferation. As Ag-specific T cells begin to expand, nonspecific T cells are depleted en masse and exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
107
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 29 publications
15
107
4
Order By: Relevance
“…Adoptively transferred cells in uninfected mice remained CFSE high and annexin V neg (data not shown). This is consistent with previously reported observations of selective depletion of T cells en masse via apoptosis in the spleens of mice infected with proinflammatory pathogens such as LM (30). Our results suggest that costimulation mediated via TNFR2 is important in rescuing Ag-specific T cells from generalized depletion that occurs during the early stages of LM infection.…”
Section: Cd8 T Cells Depend On Tnfr2 For Survival During the Early Phsupporting
confidence: 82%
“…Adoptively transferred cells in uninfected mice remained CFSE high and annexin V neg (data not shown). This is consistent with previously reported observations of selective depletion of T cells en masse via apoptosis in the spleens of mice infected with proinflammatory pathogens such as LM (30). Our results suggest that costimulation mediated via TNFR2 is important in rescuing Ag-specific T cells from generalized depletion that occurs during the early stages of LM infection.…”
Section: Cd8 T Cells Depend On Tnfr2 For Survival During the Early Phsupporting
confidence: 82%
“…Consistent with this, a previous study has shown that nonspecific T cells are depleted early during infection with Listeria. 25 Our results show that rather than being depleted, CD8 lo cells expand in infected mice, suggesting that inflammatory cytokines produced in response to infection could promote the growth of these cells in vivo.…”
Section: Bystander Proliferation Of Cd8 Lo Cells In Response To Bactementioning
confidence: 79%
“…One possibility is that early proinflammatory signals, such as IFN-␣, could trigger physiological changes that do not lead to cell cycle progression, but that sensitize lymphocytes to the actions of LLO (23). It has been reported that there is early Ag-independent activation of CD8 ϩ lymphocytes during Listeria infection (24). Ag-nonspecific lymphocytes up-regulated CD69 by day 1 postinfection, but did not up-regulate late activation markers.…”
Section: Discussionmentioning
confidence: 99%